Lebanon Public Finance Review : Ponzi Finance? - World Bank (Washington, DC, 2022)
The Public Finance Review (PFR) analyzes Lebanon’s public finances over a long horizon, to understand the roots of the fiscal profligacy and its eventual insolvency. To do so, the PFR links three critical elements in three Sections. Section I: Fiscal Policy in the Second Republic; Section II: Macro-Financial Restructuring; Section III: Public Service Non-Delivery. A fourth critical element is geopolitics, which is beyond the scope of the PFR. Taken together, these form critical determinants of the outcomes for any future socio-political-economic re-configuration.